1993
DOI: 10.1128/jb.175.7.2162-2167.1993
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Escherichia coli aromatic hydroxylase with a broad substrate range

Abstract: The hpaB gene encoding an aromatic hydroxylase of Escherichia coli ATCC 11105, a penicillin G acylase-producing strain, has been cloned and expressed in E. coli K-12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
68
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 37 publications
3
68
0
Order By: Relevance
“…This enzyme is encoded by two genes which appear to be part of the same operon (38). The homologous 4-HPA hydroxylase operon of E. coli C has been also cloned and partially sequenced (38,39). In spite of this information, some genes of the 4-HPA catabolic pathway as well as their genetic arrangement remained unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme is encoded by two genes which appear to be part of the same operon (38). The homologous 4-HPA hydroxylase operon of E. coli C has been also cloned and partially sequenced (38,39). In spite of this information, some genes of the 4-HPA catabolic pathway as well as their genetic arrangement remained unknown.…”
mentioning
confidence: 99%
“…In addition, we have previously demonstrated that the first step in the 4-HPA degradation in E. coli W, i.e., the formation of HPC, is catalyzed by a twocomponent aromatic hydroxylase (38,39). This enzyme is encoded by two genes which appear to be part of the same operon (38).…”
mentioning
confidence: 99%
“…This monooxygenase shows a broad substrate range, hydroxylating phenol derivatives (32,33). While the HpaB protein (58.7 kDa) of 4-HPA 3-monooxygenase was shown to be the oxygenase component, HpaC (18.6 kDa) was assumed to be a coupling protein that enhanced the activity of HpaB and could prevent the wasteful oxidation of NADH in the absence of substrate (32).…”
mentioning
confidence: 99%
“…The 4-hydroxyphenylacetate (4-HPA) 3-monooxygenase from Escherichia coli W is a two-component enzyme encoded by the hpaB and hpaC genes and catalyzes the initial reaction in the degradation of 4-HPA, i.e., the introduction of a second hydroxyl group into the benzene nucleus at a position ortho to the existing hydroxyl group, giving rise to 3,4-dihydroxyphenylacetate (3,4-DHPA) (32,33). This monooxygenase shows a broad substrate range, hydroxylating phenol derivatives (32,33).…”
mentioning
confidence: 99%
“…putida, R. pickettii, and Burkholderia cepacia (Prieto et al, 1993;Prieto and Garcia, 1994;Amnachalam et al, 1992Amnachalam et al, , 1994Arunachalam and Massay, 1994;Takizawa et al, 199.5;Xun, 1996). From the data compiled in Table 3, a great variety within this class of enzymes becomes obvious.…”
Section: Discussionmentioning
confidence: 99%